Integrative Knowledge and Contemporary Issues: Evaluating Amin Abdullah's Paradigm of Multidisciplinarity - Dasrizal, Budiman; Suhail, Muhammad; Pradipta, Raihan (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This study investigates the evolving nature of knowledge in addressing contemporary issues that arise with rapid societal changes. Motivated by the need for adaptive solutions beyond traditional monodisciplinary approaches, this research examines the new paradigm introduced by Amin Abdullah in his seminal work,